Tourism Communication in Community Based Tourism in Dieng Community, Central Java, Indonesia - Sunuantari, Manik (Bina Nusantara University, 2017)
To encourage a communityâs role in the field of tourism, the local government of Central Java, Indonesia promotes a Community Based Tourism (CBT) as a tourism development for the sustainable economy. It involves the community in decision-making processes, especially related to the acquisition of income, employment, and the preservation of the environment, and culture of the indigenous people. This research aimed to determine communication activities in the implementation of CBT. The theory used was tourism communication using Attention, Interest, Desire, Action (AIDA) model. Then, the method was a case study by choosing Dieng as a tourist destination, and the tourism communication activities were undertaken in Diengâs society, especially in the activities of Dieng Culture Festival (DCF). The results show that the tourism communication activities involving the community, POKDARWIS (Kelompok Sadar Wisata - Tourism Awareness Group), tourism advocates, and local governments should pay attention to the cultural and natural tourism potentials, and empower the local communities.